Production Optimization of Chlorophyll Herbs Spice Powder from Tapak Liman (Elephantopus scaber) Leaves with Response Surface Method - Andrew Setiawan Rusdianto; Triana Oktaviani Nurhardiningsih; Andi Eko Wiyono (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Jamu is a herbal drink obtained from the processing of plant parts which are non-toxic and do not have side effects. One way to extend the shelf life of herbal medicine is by changing the form of herbal medicine into powder. The method that can be used is foam mat drying which involves an emulsifying agent in the form of maltodextrin and a foam agent in the form of tween 80. Generally, herbal medicine is made from raw materials such as ginger. Ginger contains gingerols and shogaols as phenolic antioxidant components. Improving the quality, characteristics, attractiveness of herbal spice powders can be done by adding green coloring from chlorophyll. Chlorophyll is a photosynthetic pigment in plants that can absorb blue, red and purple light and reflects green in plants. Tapak liman leave (Elephantopus scaber) is one of the weeds that has a deep green color and can be used as medicine. The characteristics of herbal spice powders with chlorophyll are influenced by factors in each process, such as the mixing and drying processes. Optimizing the final result requires process engineering with one of the methods, namely the Response Surface Methodology. This study used the Behnken Box Design with 3 factors in the form of mixing time, drying time and power with a design that produced 15 treatments. Optimization response parameters used consist of response to chlorophyll content and response to water content. Optimum treatment conditions were obtained in the treatment with 26 minutes of stirring time, 10 minutes of drying time at 400 Watt power. The chlorophyll response is 14.138 ppm and the water content response is 2.5%. Analysis of herbal powder containing chlorophyll supporting optimum treatment conditions can be carried out by measuring color, pH and TDS. The L* value owned by is 73.7 which tends to be brightness. Meanwhile, the a* value is -2.5 and the b* value is 6.5. The degree of acidity or pH at is 6.03 with a total dissolved solids value of 7.75 °Brix.